Asymmetric Pedicle Subtraction Osteotomy for Adult Spinal Deformity with Coronal Imbalance: Complications, Radiographic and Surgical Outcomes. Issue 2 (19th June 2019) - Chan, Andrew K; Lau, Darryl; Osorio, Joseph A; Yue, John K; Berven, Sigurd H; Burch, Shane; Hu, Serena S; Mummaneni, Praveen V; Deviren, Vedat; Ames, Christopher P
Abstract: BACKGROUND: Asymmetric pedicle subtraction osteotomy (APSO) can be utilized for adult spinal deformity (ASD) with fixed coronal plane imbalance. There are few reports investigating outcomes following APSO and no series that include multiple revision cases. OBJECTIVE: To detail our surgical technique and experience with APSO. METHODS: All thoracolumbar ASD cases with a component of fixed, coronal plane deformity who underwent APSO from 2004 to 2016 at one institution were retrospectively reviewed. Preoperative and latest follow-up radiographic parameters and data on surgical outcomes and complications were obtained. RESULTS: Fourteen patients underwent APSO with mean follow-up of 37-mo. Ten (71.4%) were revision cases. APSO involved a mean 12-levels (range 7-25) and were associated with 3.0 L blood loss (range 1.2-4.5) and 457-min of operative time (range 283-540). Surgical complications were observed in 64.3%, including durotomy (35.7%), pleural injury (14.3%), persistent neurologic deficit (14.3%), rod fracture (7.1%), and painful iliac bolt requiring removal (7.1%). Medical complications were observed in 14.3%, comprising urosepsis and 2 cases of pneumonia. Two 90-d readmissions (14.3%) and 5 reoperations (4 patients, 28.6%) occurred. Mean thoracolumbar curve and coronal vertical axis improved from 31.5 to 16.4 degrees and 7.8 to 2.9 cm, respectively. PI-LL mismatch, mean sagittal vertical axis, and pelvic tilt improved from 40.0 to 27.9-degrees, 10.7 to 3.5-cm, and 34.4 to 28.3-degrees, respectively. CONCLUSION: The APSO, in both a revision and non-revision ASD population, provides excellent restoration of coronal balance—in addition to sagittal and pelvic parameters. Employment of APSO must be balanced with the associated surgical complication rate (64.3%).